اسلامی ریاست کے نظام تعلیم کا جائزہ کلام اقبال کی روشنی میں: A review of the education system of the Islamic State in the light of Iqbal's words - Shahrukh Khan; Noshen Akhtar (DIRAYAT, 2024)
This article explores the multifaceted role of Allama Iqbal as both a celebrated poet and a dedicated advocate of Islam. Through an analysis of his poetry, the paper examines how Iqbal presents Islam as a solution to contemporary challenges, emphasizing the concept of an Islamic state infused with divine principles. Additionally, it delves into Iqbal's advocacy for the integration of modern sciences into society, highlighting their importance for educational and societal advancement. The abstract also discusses Iqbal's efforts to merge religious and modern sciences, urging the youth to embrace these disciplines amidst prevailing materialism. Furthermore, it underscores the critical role of education within an Islamic state, as emphasized by Iqbal, who advocates for a balanced approach encompassing both religious and scientific education. Through an exploration of Iqbal's writings, the article elucidates the educational responsibilities of an Islamic state and its contribution to the advancement of both modern and religious sciences. Key terms: Allama Iqbal, Islam, poetry, Islamic state, modern sciences, religious sciences, education.